Effects of Multimedia Assisted Song Integrated Teaching on College Students' English Learning Interests and Learning Outcomes - Luo, Yu-Zhou; Kong, Xiang-Yang; Ma, Yu-Yang (Frontiers in Psychology, 2022)
In the process of globalization, English not only represents British and American culture, but also gradually becomes a language widely used all over the world, which is essential to learn as a second language. In this case, the necessity of learning English is inevitable and cannot be ignored. Education is the century business of a nation. In order to cope with the E generation, I generation, and touch-screen generation students, more and more teachers are involved in multimedia-integrated curriculum design and instruction. Teachers are no longer just knowledge providers, but they are expected to provide students with a personal learning model and guide and support them in a timely manner. The sample of the study was composed of the business students in Guilin University of technology. A total of 216 students participated in a 16-week (3 hours per week, a total of 48 hours) experimental teaching. The research results showed that 1. multimedia assisted, song integrated English teaching affected learning interest, 2. multimedia assisted, song integrated English teaching affected learning outcome, and 3. learning interest had significantly positive effects on learning outcome. Based on the results, it is expected that this study can contribute to improving college students’ English listening, speaking, reading, and writing skills multimedia teaching. In addition, it is safe to claim that their English learning interest and learning outcome can be facilitated through multimedia teaching.